UJI COBA PEMULIHAN GIZI BURUK CARA KLINIK GIZI PUSLITBANG GIZI DI POSYANDU - Djoko Kartono; Sandjaja Sandjaja; Susi Suwarti Suwardi; Amelia Amelia; Suhartato Suhartato (Persagi, 2001)
Trial The Management of Severe Malnourished Children of Nutrition Clinic Method, The Nutrition Research and Development Centre at Village Level.Background: Managerrent of severe malnutrition recommended by WHO should be in hospital. For family with severe malnourished child, generally poor, hospitalization means spend a lot of money. The alternative method is the out patient management developed by Nutrition Clinic of the Nutrition Research ard Development Centre.Objectives: To study the effectiveneess of management for severe malnourished of Nutrition Clinic method in village level (posyandu) by village cadre.Methods: The study was carried out at 4 sub-districts in Bogor and Sukabumi, West Java. Sixty under-five children for group 1 and 60 for group 2 were selected. Three to five posyandu's cadres were selected in each village. Visit schedule to posyandu for group 1 was similar to that Nutrition Clinic while group 2 was every 1 week. Nutrition package for group 1 and 2 was same. Data collection included body measurements, morbiddity and food consumption. Observation to the cadres performance include ownership and he use of guidance book.Results: Seven percent of children aged 6-11 months, 20% aged 12-17 months, 60% aged 18-35 months and 13% aged > 36 months. Around 30% of children had been grven fruit and porridge on the age 1-4 months old. Nutritional status improved variously depended on the nutritional indices. Energy consumption was low but protein consumption had reached the recommended allowance. Compliance to come to posyandu and nutrition package was high.Conclusions: Around 10% of cchildren had changed from under-weight to well-nourished, but most of severe malnourished children remained severe in 3 months. Stunted was over 75% and remained stunted in 3 months. Wasted was 50% and began to decline in 3 months. The average of weight increment in 3 months was 0,6 kg. Cadre could give simple education to mothers using the available guidance book.Recommendations: To use wasted as an indicator in the evaluation of management of severe malnutrition. Active role of health Centre is needed to have maximum effect of the implementation of Nutrition Clinic method at village level.Key words: management, severe malnutrition, nutrition clinic, out-patient, village cadre.